Investigating the Impact of Ownership Structure and Board Composition on the Technical Efficiency of the Listed Companies on the Tehran Stock Exchange (Shahid Bahonar University of Kerman, 2013)
Abstract The purpose of this article is to investigate the impact of ownership structure and board composition on the technical efficiency of the listed companies on the Tehran Stock Exchange. In attempting this, the technical efficiency of the examined companies was first determined by using Data Envelopment Analysis (DEA). Then, the relationship between ownership concentration, institutional ownership, board composition and technical efficiency was investigated. The data sample is restricted to 82 companies during an 8 years period from 1381 to 1388. The results of hypothesis testing using Panel Data Regression indicate that there is a significant positive relationship between institutional ownership and technical efficiency even after controlling for potential confounding factors. However, the relationship between ownership concentration, board composition and technical efficiency is positive and insignificant. When the impact of all these corporate mechanisms was considered together, the preceding results holds true. This finding is consistent with the active monitoring hypothesis, indicating that institutional ownership play a significant role in monitoring management and reducing the agency costs.